2004
DOI: 10.1093/hmg/ddh181
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional consequences of glutamine tract variation in the androgen receptor

Abstract: The androgen receptor (AR) gene contains a polymorphic trinucleotide repeat region, (CAG)(n), in its N-terminal transactivation domain (NTD) that encodes a polyglutamine (polyQ) tract in the receptor protein. Whereas the length of the CAG repeat ranges from 6 to 39 in healthy individuals, the variations in repeat length both within and outside the normal range are associated with disease, including impaired spermatogenesis and Kennedy's disease, and with the risk of developing breast and prostate cancer. Where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
188
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(203 citation statements)
references
References 87 publications
11
188
0
3
Order By: Relevance
“…A more recent study (Buchanan et al 2004) reveals that under a critical size of 16 CAG repeats, the conformational structure resulting from the short polyglutamine tract encoded by these repeats could enhance the binding of specific transcriptional coactivators, resulting in higher AR activity even at lower androgen concentrations. The Ivory Coast and all North African samples show high frequencies of CAG alleles £ 18 repeats.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study (Buchanan et al 2004) reveals that under a critical size of 16 CAG repeats, the conformational structure resulting from the short polyglutamine tract encoded by these repeats could enhance the binding of specific transcriptional coactivators, resulting in higher AR activity even at lower androgen concentrations. The Ivory Coast and all North African samples show high frequencies of CAG alleles £ 18 repeats.…”
Section: Discussionmentioning
confidence: 99%
“…Normal CAG repeat number varies from 11 to 36 [9]. Previous studies in vitro have demonstrated that CAG repeat number shows an inverse correlation with AR activity [9][10][11][12][13][14]. Hence, it's not difficult to understand that shorter CAG repeats, increasing AR activity, are associated with prostate cancer [15,16], hirsutism [17] and hyperandrogenism in ovary [18,19], while longer CAG repeats, decreasing AR activity, are related to hypoandrogenicity [20] and male infertility due to impaired sperm production [10,21].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas extreme CAG lengths (>40 repeats) cause spinal muscular atrophy (i.e., Kennedy disease), a higher number of repeats within the normal range (>90% alleles have between 16 and 29 CAG repeats) have been associated with lower androgen receptor transactivational capacity in numerous in vitro studies (27)(28)(29)(30)(31), and with androgenic phenotypes in transgenic mice (32). In humans, shorter CAG lengths have been associated with accentuation of several sexually differentiated somatic phenotypes in males (33) and with the presence of hyperandrogenic syndromes in females (34) (although negative studies also exist e.g., ref.…”
mentioning
confidence: 99%